Survival Following Segmentectomy or Lobectomy in Patients With Stage IB Non-small-cell Lung Cancer - Hao, Bo; Zhang, Lin; Fan, Tao; Liu, Bohao; Jiang, Wenyang; Hu, Hao; Geng, Qing (Frontiers in Oncology, 2020)
Background: Lobectomy with mediastinal lymph node dissection has always been recognized as the standardized treatment for early-stage non-small-cell lung cancer. However, the feasibility of segmentectomy performed in stage IB non-small-cell lung cancer (NSCLC) patients remains controversial. The present study aims to investigate whether the outcome of stage IB NSCLC patients undergoing segmentectomy was comparable to those who underwent lobectomy. Method: We retrospectively collected data of 11,010 patients with primary stage IB non-small-cell lung cancer from the Surveillance, Epidemiology, and End Results database. Overall survival (OS) and lung cancer-specific survival (LCSS) were assessed among patients who were performed lobectomy or segmentectomy. To further assess the impact of the surgical procedures on patients with different tumor sizes, subgroups stratified by tumor size were analyzed. Results: A total of 11,010 patients who were pathologically confirmed to be stage IB were included, of whom 10,453 received lobectomy and 557 received segmentectomy. Both univariate and multivariate Cox regression analyses showed that the patients receiving lobectomy had better OS [hazards ratio (HR) = 1.197, 95% confidence interval (CI) (1.066, 1.343), P < 0.001] than those receiving segmentectomy. However, multivariate analysis showed that there was no significant difference in LCSS between lobectomy and segmentectomy [HR = 1.172, 95% CI (0.963, 1.427), P = 0.114]. Meanwhile, subgroup analyses showed that lobectomy rather than segmentectomy was associated with better OS [HR = 1.278, 95% CI (1.075, 1.520) P = 0.006] and LCSS [HR = 1.118, 95% CI (1.005, 1.280), P = 0.047] for patients with a tumor size (TS) of ≤ 40 and >30 mm, while for patients with a TS of ≤ 30 mm, lobectomy yielded similar OS [TS ≤ 20 mm: HR = 1.068, 95% CI (0.853, 1.336), P = 0.566; TS > 20 mm and ≤ 30 mm: HR = 1.195, 95% CI (0.961, 1.487), P = 0.109] and LCSS [TS ≤ 20 mm: HR = 1.029, 95% CI: (0.682, 1.552), P = 0.893; TS > 20 and ≤ 30 mm: HR = 1.144, 95% CI (0.795, 1.645), P = 0.469] to that of segmentectomy. Conclusion: Segmentectomy achieved equivalent OS and LCSS in stage IB NSCLC patients with TS ≤ 30 mm compared with lobectomy. Lobectomy showed better OS and LCSS than segmentectomy for patients with a TS of >30 and ≤ 40 mm. Segmentectomy may be acceptable in patients with an older age and a smaller TS.